2020
DOI: 10.1001/jamanetworkopen.2020.26881
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Racial/Ethnic Disparities in Hospitalization and Mortality in Patients With COVID-19 in New York City

Abstract: IMPORTANCE Black and Hispanic populations have higher rates of coronavirus disease 2019 hospitalization and mortality than White populations but lower in-hospital case-fatality rates. The extent to which neighborhood characteristics and comorbidity explain these disparities is unclear. Outcomes in Asian American populations have not been explored. OBJECTIVETo compare COVID-19 outcomes based on race and ethnicity and assess the association of any disparities with comorbidity and neighborhood characteristics. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
281
12
2

Year Published

2021
2021
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(328 citation statements)
references
References 32 publications
24
281
12
2
Order By: Relevance
“…Unmeasured or otherwise undetected subclinical risk factors may also be driving the persistent disparities 34 35 Notably, at least one prior study of racial/ethnic disparities in COVID-19 severity, involving over 2600 patients hospitalised in New York City during the first few months of the pandemic, paradoxically found that NHBs and Hispanic/Latinx patients had less illness severity than NHW patients. 36 In accordance with other studies reporting more affluent and travelled individuals more affected earlier in the pandemic, 37 followed by less affluent and more essential worker individuals increasingly affected later in the pandemic, 33 severity of COVID-19 illness may be determined by relative dose, type, timing and chronicity of SARS-CoV-2 exposure on top of factors specific to race/ ethnicity and SES. Several limitations to our study merit consideration.…”
Section: Discussionsupporting
confidence: 83%
“…Unmeasured or otherwise undetected subclinical risk factors may also be driving the persistent disparities 34 35 Notably, at least one prior study of racial/ethnic disparities in COVID-19 severity, involving over 2600 patients hospitalised in New York City during the first few months of the pandemic, paradoxically found that NHBs and Hispanic/Latinx patients had less illness severity than NHW patients. 36 In accordance with other studies reporting more affluent and travelled individuals more affected earlier in the pandemic, 37 followed by less affluent and more essential worker individuals increasingly affected later in the pandemic, 33 severity of COVID-19 illness may be determined by relative dose, type, timing and chronicity of SARS-CoV-2 exposure on top of factors specific to race/ ethnicity and SES. Several limitations to our study merit consideration.…”
Section: Discussionsupporting
confidence: 83%
“…A large cohort study of patients within a large health system in New York City found among patients hospitalized for COVID-19, that Black patients were even less likely than White patients to have severe illness and to die or be discharged to hospice. 94 In agreement with another study focusing on black non-Hispanic and white non-Hispanic patients 12 a study in an health care system in the United States including almost 3.5 Million members, revealed that race among White, Black, Hispanic, and Asian participants was the most important predictor of SARS-CoV-2 infection and hospitalization due to COVID-19 but not for mortality. 96 Thus, it appears that specific race/ethnic groups of patients are not inherently more susceptible to having poorer COVID-19 outcomes than other ethnic groups.…”
Section: Role Of Hypertension and Its Association With Age Race/ethnsupporting
confidence: 69%
“… 18 This indicates that differences in hypertension together with differential patterns of other comorbidities including obesity, diabetes, and CKD could impact on outcome in COVID-19 in specific race/ethnic groups. 94 In the large cohort of 7868 hospitalized patients from the American Heart Association COVID-19 Cardiovascular Disease Registry, Hispanic and non-Hispanic Black patients accounted for 58.5% of all patients hospitalized and bore a greater burden of mortality and morbidity. 95 However, race/ethnicity was not independently associated with worse in-hospital mortality or major cardiovascular events after adjustment.…”
Section: Role Of Hypertension and Its Association With Age Race/ethnmentioning
confidence: 99%
See 1 more Smart Citation
“…Mortality was defined based on the discharge disposition of the first COVID-19 hospitalization. Consistent with other studies, [24][25][26] we used a composite endpoint of in-hospital mortality, transfer to inpatient hospice or discharge to facility or home-based hospice to define our outcome of early mortality.…”
Section: Study Outcomementioning
confidence: 99%